Multi-Isotope Geochemical Baseline Study of the Carbon Management Canada Research Institutes CCS Field Research Station (Alberta, Canada), Prior to CO2 Injection - Rachel E. Utley; Emma Martin-Roberts; Nicholas Utting; Gareth Johnson; Domokos Györe; Marta Zurakowska; Finlay M. Stuart; Adrian J. Boyce; Thomas H. Darrah; Pauline Gulliver; R. Stuart Haszeldine; Don Lawton; et al. (Earth Science, Systems and Society)
Carbon capture and storage (CCS) is an industrial scale mitigation strategy for reducing anthropogenic CO2 from entering the atmosphere. However, for CCS to be routinely deployed, it is critical that the security of the stored CO2 can be verified and that unplanned migration from a storage site can be identified. A number of geochemical monitoring tools have been developed for this purpose, however, their effectiveness critically depends on robust geochemical baselines being established prior to CO2 injection. Here we present the first multi-well gas and groundwater characterisation of the geochemical baseline at the Carbon Management Canada Research Institutes Field Research Station. We find that all gases exhibit CO2 concentrations that are below 1%, implying that bulk gas monitoring may be an effective first step to identify CO2 migration. However, we also find that predominantly biogenic CH4 (∼90%–99%) is pervasive in both groundwater and gases within the shallow succession, which contain numerous coal seams. Hence, it is probable that any upwardly migrating CO2 could be absorbed onto the coal seams, displacing CH4. Importantly, 4He concentrations in all gas samples lie on a mixing line between the atmosphere and the elevated 4He concentration present in a hydrocarbon well sampled from a reservoir located below the Field Research Station (FRS) implying a diffusive or advective crustal flux of 4He at the site. In contrast, the measured 4He concentrations in shallow groundwaters at the site are much lower and may be explained by gas loss from the system or in situ production generated by radioactive decay of U and Th within the host rocks. Additionally, the injected CO2 is low in He, Ne and Ar concentrations, yet enriched in 84Kr and 132Xe relative to 36Ar, highlighting that inherent noble gas isotopic fingerprints could be effective as a distinct geochemical tracer of injected CO2 at the FRS.